Should we fear the robot revolution? (the correct answer is yes) - Berg, Andrew; Buffie, Edward F.; Zanna, Luis-Felipe (Washington, DC, 2018)
"We may be on the cusp of a “second industrial revolution” based on advances in artificial intelligence and robotics. We analyze the implications for inequality and output, using a model with two assumptions: “robot” capital is distinct from traditional capital in its degree of substitutability with human labor; and only capitalists and skilled workers save. We analyze a range of variants that reflect widely different views of how automation may transform the labor market. Our main results are surprisingly robust: automation is good for growth and bad for equality; in the benchmark model real wages fall in the short run and eventually rise, but “eventually” can easily take generations."